Differences in Liver Graft Survival by Recipient Sex. Issue 12 (December 2020) - De Simone, Alexia I.; Zhang, Xun; Dahhou, Mourad; Sapir-Pichhadze, Ruth; Cardinal, Heloise; Ng, Vicky; Foster, Bethany J.
Abstract : Background: We aimed to characterize patterns of differences in liver graft failure rates by recipient sex, accounting for the modifying effects of donor sex and recipient age. Methods: We evaluated 144 212 first deceased donor liver transplant recipients [1988–2019; Scientific Registry of Transplant Recipients (SRTR)]. We used multivariable time-varying Cox models, considering a recipient sex by donor sex by recipient age (0–12, 13–24, 25–44, ≥45 y) interaction. Results: Among recipients of male donors, females <45 y had higher graft failure rates than males of the same age, but none of these differences were statistically significant [0–12 y: adjusted hazard ratio (aHR) 1.17 (0.98, 1.40); 13–24 y: aHR 1.18 (0.96, 1.46); 25–44 y: aHR 1.11 (0.96, 1.28)]; there was no material or statistically significant difference between female and male recipients ≥45 y [aHR 1.01 (0.97, 1.06)]. When the donor was female, recipients <45 y showed no statistically significant differences in graft outcomes by recipient sex [0–12 y: aHR 0.91 (0.74, 1.11); 13–24 y: aHR 0.98 (0.77, 1.25); 25–44 y: aHR 0.86 (0.73, 1.01)], whereas female recipients ≥45 y had significantly lower graft failure rates [aHR 0.85 (0.81, 0.89)] than males of the same age. Conclusions: Among recipients of female donors, female recipients ≥45 y had significantly better outcomes than males of the same age; there were no clear differences by recipient sex in younger recipients. When the donor was male, there was no material or statistically significant difference in graft failure rates between males and females ≥45 y; among younger recipients point estimates suggested higher failure rates in females than males recipients, but confidence intervals were wide making firm conclusions impossible. Larger studies combining multiple datasets are needed. Abstract : Supplemental Digital Content is available in the text.